Local Culture as a Resource in Regional Development in the Southwest-Finland Archipelago - Katriina Siivonen (Journal of Ethnology and Folkloristics)
In cultural and regional politics in the European Union, and in practice for instance in the Southwest-Finland Archipelago, local culture and cultural heritage are considered resources. Global boundlessness, heterogeneity and change are basic qualities of culture. However, in regional development, culture is seen and used as a number of different local cultures with their own essential cultural heritage. The culture of local everyday life is opposite to, and in tension with, the construct of cultures used in regional development. Accordingly, culture should primarily be safeguarded as a heterogenic, dynamic and interactive process of everyday life. This process is the most important resource of local culture. In addition, culture should be safeguarded as value-based cultural constructions, such as brands or common identities of certain cultures, with for instance cultural heritage as a part of it. In the latter case, a common, transparent definition of these brands, identities and cultural heritages with their different values, is needed.